Curriculum Evaluation of Entrepreneurship Education: Employers’ Feedback on Business Graduates’ Job Performance - Gretchen Dawaton Bangguiyac; Daniel Pannogan; Sonia Belinan; Karen Razelle Duyan (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aimed to evaluate employers’ feedback on the job performance of Bachelor of Science in Entrepreneurship graduates of Kalinga State University (KSU) to identify strengths and areas for improvement across four competency domains: personal, interpersonal, intellectual, and technical. The findings serve as a basis for curriculum enhancement, instructional innovation, and career development initiatives, thereby reinforcing educational accountability and employability outcomes within the ASEAN context. Methodology: The study employed a mixed-method research design integrating quantitative and qualitative approaches. A descriptive survey using a structured questionnaire distributed via Google Forms and in-person administration was utilized. Data was encoded in Microsoft Excel and analyzed using descriptive statistics such as frequency, percentage, weighted mean, and ranking, complemented by thematic analysis of employers’ qualitative feedback. Main Findings: Quantitative results indicated that graduates performed very satisfactorily in all four domains: personal abilities (M = 4.32), interpersonal abilities (M = 4.15), intellectual abilities (M = 4.19), and generic and specific knowledge and skills (M = 3.92). Employers commended graduates’ persistence, teamwork, and creativity but emphasized the need to improve communication, leadership, and digital literacy. The qualitative results revealed four major themes: practical and experiential learning, communication and interpersonal development, technological and digital skills enhancement, and leadership and professional competence. Novelty/Originality of this study: This study provides empirical evidence linking employer feedback with curriculum evaluation through the CIPP (Context–Input–Process–Product) Model, a framework rarely applied in Philippine entrepreneurship education research. It advances discourse on educational assessment and accountability by positioning employer perspectives as outcome-based indicators of curricular effectiveness. Moreover, it contributes to the ASEAN goal of promoting quality-assured, outcome-based, and employability-driven higher education that prepares graduates to be innovative, globally competent, and industry-responsive.